Pengaruh Foot Exercise Terhadap Neuropati Motorik Pada Pasien DM Tipe 2 Di Wilayah Kerja Puskesmas Benteng - Mareta Herdiyani; Erna Safariyah; Arfatul Makiyah (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Diabetes Mellitus is a chronic, progressive disease characterized by the body's inability to metabolize carbohydrates, fats and proteins, leading to hyperglycemia. DM can be associated with serious complications such as kidney damage, eye problems, cardiovascular disease, nerve damage and skin and foot problems, so DM sufferers need to take precautions to avoid complications. Foot exercise is a type of foot exercise performed by diabetics which can increase peripheral perfusion and thus prevent worsening of diabetic neuropathy. Foot exercise can also reduce the risk and progression of peripheral neuropathy because it can improve blood flow to the periphery, increase muscle strength and improve motor function. Objective: to determine the effect of foot exercise on motor neuropathy in type 2 DM patients. Method: The design in this study used a quasi-experimental approach using a one group pretest posttest design. The sample for this research was 18 respondents. Data analysis used the paired sample t-test. Results: based on the results of statistical tests using the Paired Samples t Test, the resulting P value is 0.000 < 0.05, where it can be concluded that there is an influence of foot exercise on Motor Neuropathy in type 2 DM patients. Conclusion: It can be concluded that there is an influence of foot exercise on Motor Neuropathy in type 2 DM patients in the working area of Benteng Sukabumi City Health Center.